Water to cyclohexane transfer free energy calculations for a carbon nanotube. (October 2022) - Gotzias, Anastasios
Graphical abstract: Abstract: We calculate the difference in the solvation free energy of a carbon nanotube in water and cyclohexane and introduce two methods to perform these calculations. One is to use thermodynamic integration and gradually decouple the interactions of the nanotube with these solvents. The other is to build a water–cyclohexane system and create a transition path for the nanotube on a direction normal to the water–cyclohexane interface, and employ umbrella sampling simulations on the path and calculate the free energy difference between the states. By combining the solvation free energies of the nanotube computed by thermodynamic integration, we infer correlations with the free energies of transfering the nanotube directly from the one solvent to the other, computed by umbrella simulations. The correlations depend on how many molecules of the one solvent partition into the other together with the nanotube. We measure this amount by averaging the water accessible surface area of the nanotube over the umbrella sampling simulations. When the direction is from cyclohexane to water, cyclohexane molecules are coextracted with the nanotube into the water phase. These molecules remain adsorbed inside the pore, even when the nanotube enters adequately the aqueous solution. The adsorbed phase of cyclohexane configures an almost complete monolayer over the internal surface of the nanotube making it inaccessible to water.